Study on the extraction of flavonoids from Artemisia integrifolia and its anti-lung cancer activity - Wang Chunyang; Fu Shuang; Zhu Ruidong; Cao Hongyan; Zhao Jiangyang (BIO Web of Conferences)
Objective: To extract flavonoids from Artemisia integrifolia and determine their content, to evaluate their activity. Method: Total flavonoids were extracted using ultrasonic extraction, and the inhibitory effect on the proliferation of lung cancer cells H1299 was investigated. Additionally, a preliminary study was conducted on the treatment of liver degeneration. Results: Using a 50% ethanol solution, ultrasonic treatment at 90°C for 50 minutes followed by reflux for 3 hours resulted in the highest total flavonoid extraction rate. The study showed that it has a certain inhibitory effect on the proliferation of lung cancer H1299 cells, with an IC50 value of approximately 200μg/mL measured by MTT assay. The treatment also showed therapeutic effects on liver degeneration.